Factors influencing self-reported use of antioxidant supplements in patients with age-related macular degeneration - Yu, Alice L.; Paul, Tobias; Schaumberger, Markus; Welge-Lüssen, Ulrich-Christoph (Current Eye Research, 2014)
Abstract Aim: The goals of the present study were to evaluate the current use and accuracy of dose-taking prescription among patients with age-related macular degeneration (AMD) and to detect potential factors influencing the use or non-use of oral antioxidant supplements.This is a cross-sectional questionnaire-based study of 65 patients with AMD of Age-Related Eye Disease Study (AREDS) category 3 (intermediate AMD) or category 4 (unilateral advanced AMD). Self-report data were obtained from a structural clinical interview in clinic. The patients were asked questions regarding their demographic, ophthalmologic and systemic data, their source of recommendation for antioxidant supplement use and/or their reasons for non-use. Afterwards, this information was correlated with the use or non-use of antioxidant supplements. Statistical analyses were conducted using a series of Mann-Whitney U-tests and Fisher's exact tests.There were 55.4% (36 of 65) of the patients reporting antioxidant supplement use for AMD and 44.6% (29 of 65) with no supplement use. However, only 56.7% (17 of 30) took the recommended dose on label. There were significantly more female patients taking supplements than male patients (p = 0.010). A statistically significant correlation was also found between supplement use and the number of visits to an ophthalmologist per year (p = 0.037). The main reason for antioxidant supplement non-use was the missing awareness of the availability of antioxidant supplements.Despite the recommendation of oral antioxidant supplements in the ARED Study for patients with AMD of category 3 or 4, only about half of these patients took the supplements in this study. Identifying the factors, which influenced the decision against supplement use, may help to better support patients in the prevention of severe vision loss caused by AMD.
EVALuna2:21196